TREN PENDIDIKAN MATEMATIKA BERDASARKAN PERUBAHAN KURIKULUM DARI TAHUN 2006 SAMPAI DENGAN 2024 TINGKAT SMA - Ramadhani, Nadya; Siregar, Jodi Mahmud; Rajaguguk, Waminton (Jurusan Ilmu Pendidikan FKIP Universitas Mataram, 2024)
Mathematics education at the high school level has an important role in preparing students to continue their studies or enter the world of work. To improve its quality, the Indonesian government has made several curriculum changes, including the 2006 Education Unit Level Curriculum (KTSP), the 2013 Curriculum, and the 2020 Merdeka Belajar Curriculum. This research aims to analyze trends in mathematics education at the high school level based on curriculum changes from 2006 to 2024 , by identifying and analyzing changes in material aspects, learning approaches, and assessments, and evaluating their impact on the quality of high school mathematics education. Using the literature research method, data was obtained from journal articles, books, research reports, policy documents and other relevant literature which were analyzed qualitatively. The research results show a shift in focus in material, learning approaches, and assessment systems along with curriculum changes, where in general the mathematics learning outcomes of high school students have increased but there are still implementation challenges in the field. Curriculum changes also have an impact on improving students' skills in critical thinking, problem solving, collaboration, communication, creativity, and the use of digital technology in mathematics learning. Despite the challenges, curriculum changes provide opportunities to improve the quality of mathematics education and develop 21st century skills.